Pelatihan Pengujian Inclining (Inclining Test) Kapal Kayu dengan Adanya Penambahan Panjang Kapal dan Berlunas Baja Bagi Pengrajin Kapal di Kabupaten Takalar - Mansyur Hasbullah; Suandar Baso; Lukman Bochary; Rosmani -; Ganding Sitepu; Syamsul Asri; Wihdat Djafar; Andi Dian Eka Anggriani; A Ardianti; Muhammad Akbar Asis (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
Transformation in ship geometry and the development of alternative materials to replace wood will certainly have an impact on the weight of construction, these changes will certainly affect the center of gravity and ship draft, such as wooden ships with steel frames which are made by wooden ship craftsmen in Takalar Regency, after being replaced with steel frame, laden increases with an increase in the draft will affect the hydrostatic characteristics of the ship and the ship's center of gravity, the change, of course, has an impact on the stability of the ship, so an inclining test is needed, so that wooden ship craftsmen can understand the relationship between ship geometry and ship weight. Therefore, in an effort to increase the knowledge of wooden ship craftsmen, inclining test training is a solution and is proposed for community service activities with method of presenting material and practicing directly on ships, the results of this training craftsmen are able to understand the emphasis on steel-constructed wooden ships in relation to life safety at sea and skilled in inclining to test.